Analisis Assesment dalam Pendidikan Inklusi di SDIT Dauroh - Septy Nurfadhilah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Inclusive education is a government program in seeking an equal education system without any discrimination or distinction between normal students and students with special needs in the same class so that they are able to obtain a decent education equivalent to the education obtained by other students in general. Inclusive education has special learning tools in order to be able to carry out the learning process intensively in accordance with the objectives of inclusive education. One of them is the use of assessment in the individual and group assessment process in the learning process. The research method used in this study is a qualitative descriptive approach with the research objective of examining the implementation of appropriate assessments in their application to inclusive education programs. The results of the study indicate that the assessment in inclusive education is an academic assessment consisting of academic, non-academic and developmental assessments and developmental assessments consisting of students' perceptions, language and motor skills